Neoadjuvant Lenvatinib in Advanced Unresectable Thyroid Carcinoma: Case Series and Literature Review - Albert, Albert; Manginstar, Christian O.; Saleh, Denny; Merung, Marselus A. (Universitas Sam Ratulangi, 2025)
Abstract: Lenvatinib, a tyrosine kinase inhibitor (TKI), has shown potential as a neoadjuvant therapy for inoperable thyroid cancer (TC). In this case series, we present three patients with unresectable thyroid tumors who responded favorably to lenvatinib treatment. A 60-year-old male with papillary thyroid cancer (PTC) experienced a 60% tumor volume reduction after five months of therapy. A 61-year-old male with medullary thyroid cancer (MTC) saw a 99% reduction after four months of lenvatinib and decrease of serum calcitonin and no residual disease six months after surgery. Lastly, a 67-year-old female with anaplastic thyroid cancer (ATC) showed a 70% tumor reduction and significant symptomatic relief. These cases highlight lenvatinib’s efficacy in reducing tumor size and stabilizing disease, improving surgical outcomes in patients initially deemed inoperable due to locally advanced tumors. Lenvatinib’s antitumor effects, driven by its antiangiogenic properties, suggest its potential as a valuable neoadjuvant treatment option in advanced thyroid cancer. Keywords: thyroid carcinoma; lenvatinib; case series